Self-healing topology for DDoS attack identification & discovery protocol in software-defined networks. (17th November 2021) - Sharma, Gajanand; Sharma, Himanshu; Pareek, Rajneesh; Gour, Nidhi; Sharma, Ravi Shanker; Kumar, Ashutosh
Abstract: Software defined networking is an emerging network architecture that separates the control plane from the data plane of network devices and places the control plane on one or more control servers capable of managing the rules traffic forwarding of all communication devices under your domain. This article describes the architecture, different modules, and event sequences of the HyPASS for real-time protection from address-forged attacks with proactive host discovery and address validation. Such attacks cause the wastage of network bandwidth, processing power, and network resources available to the user. We performed the latency, throughput, and attack prevention tests using POX & RYU controllers on the Mininet network simulator with and without HyPASS. The system performance is analyzed for accuracy and efficiency in four different SDN scenarios categorized as fully OpenFlow enabled and Hybrid. The proposed system discovers all the live hosts in the network, updates Host Table at the handshaking between controller and OpenFlow switches. Experiments show that the system prevented all the address-forged attacks by validating the source address in different SDN environments. It achieves a 99.99% filtering accuracy level in a fully OpenFlow-enabled setup.